A study to evaluate the role of suction drains in orthopedic surgery - Khanal, GP; Rijal, R; Shrestha, BP; Karn, NK; Chaudhary, P (Health Renaissance, 2011)
Background: There is controversy in routine use of suction drain in orthopedic surgeries. Devastating postoperative infection and years of treatment had forced on extra measures of postoperative wound care and use of drains. Objective: To find out the necessity of intraoperative drains in routine orthopedic surgery. Methods: Thirty patients were enrolled in the study. All of the patients were followed up on 2nd, 14th days and 3 monthly till one year of period. All the demographic data and preoperative investigations and intraoperative and postoperative parameters were recorded in standard proforma. Data were analysed using appropriate statistical method. Results: All the patients were followed up to one year period. Six patients had superficial infection on 2nd postoperative day. They were managed with antibiotics and no patient showed signs of infections on 14th postoperative day and thereafter. No patient needed postoperative reinforcement of dressing. Conclusion: Routine use of intraoperative drain in hip surgeries has beneficial effect of decreasing reinforcement of postoperative dressing. Keywords: orthopedic surgery; suction drain; BPKIHS DOI: http://dx.doi.org/10.3126/hren.v9i2.4980 Health Renaissance 2011: Vol.9 (No.2): 91-94